Forward trading and collusion in supply functions - Nikolas Wölfing (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
This paper studies the effect of forward contracts on the stability of collusion among firms, competing in supply functions on the spot market. A forward market can increase the range of discount factors which allow to sustain collusion. On the contrary, collusion is destabilised when a potential deviator sells a significant amount forward. Results do not depend on the type (financial or physical) of contract fulfilment and are robust to different levels of demand uncertainty. As a policy implication, the study finds that liquid and anonymous forward markets are incompatible with collusion.
Keywords: C73; D43; L13; G13; 330; forward trading; collusion; supply function equilibrium